A technocratic road to spatial justice? The standard as planning knowledge and the making of postwar Sweden's welfare landscapes. Issue 3 (3rd July 2022) - Pries, Johan
ABSTRACT: This article analyses the politics of spatial justice in the knowledge-making practices of planning expertise in postwar Sweden. The paper traces the genealogy of 'standards' in modern Swedish planning, arguing that this was a fundamental form of planning knowledge which came to articulate a 'universalist' politics of justice. Standards were constructed as a way to measure and make complex calculations about a range of 'needs', making the overarching goal of planning to address the universal human needs measured by standards. This technocratic articulation of justice had limitations. Standards often proved difficult for grassroots groups to contest this expertise, but were a mode of knowledge well-suited to corporate interests looking to influence planners to make space for their standardized consumer products. These tensions came to the fore in the planning of postwar Sweden's green outdoor spaces, where the standards for car users played a crucial role in shaping the landscape and planners hesitated to define national standards for areas such as parks and green space provision. Expert knowledge such as standards might, then, be a powerful tool to systematically shape space according to a particular articulation of justice, yet Sweden's technocratic road to spatial justice also exemplifies the dangers of this approach.